Electrodeposited amorphous nickel–iron phosphide and sulfide derived films for electrocatalytic oxygen evolution. (15th December 2022) - Wang, Chao; Wu, Yili; Zhou, Zixiang; Wang, Jinlian; Pei, Shaotong; Liu, Shuling
Abstract: The preparation of inexpensive and efficient electrocatalysts for oxygen evolution reaction (OER) is crucial in the widespread application of water electrolyzers. A simple one-step aqueous electrodeposition method is utilized to prepare amorphous nickel-iron sulfide (Ni–Fe–S) and phosphide (Ni–Fe–P) films on Ni foam. The deposited films are highly porous, and can convert to active electrocatalysts for OER. In 1 M KOH, the Ni–Fe–S shows the highest OER activity, and requires only 230 mV overpotential to reach 0.05 A cm −2 OER current densities. The Fe–Ni–S also sustains the 30 h 0.05 A cm −2 galvanostatic OER test. Ex-situ characterizations show that sulfur in the Fe–Ni–S is oxidized and leached into the solution during OER, and that (oxy)hydroxide layer is formed at the surface. The adsorption energy of the hydroxyl group, an OER intermediate, is tuned by the electron interaction between the Ni and Fe, and the Ni–Fe–S exhibits the optimum hydroxyl group adsorption energy and the most facile OER kinetics. Also, higher intrinsic OER activity is observed for the electrodeposited amorphous nickel phosphide-derived film than the amorphous nickel sulfide-derived film. Graphical abstract: Image 1 Highlights: One-step electrodeposition of Ni–Fe sulfide and phosphide films on Ni foam. The Ni–Fe–S shows the highest OER activity, with 0.23 V overpotential at 0.05 A cm −2 . The electron interaction tunes the hydroxyl adsorption energy and accelerates OER. Nickel phosphide exhibits higher intrinsic OER activities than nickel sulfide.